Analisis Penggunaan Mesin Electronic Data Capture (EDC) Pada Wajib Pajak Restoran Sebagai Upaya Mengoptimalkan Penerimaan Pajak Daerah di Kota Kupang - Yusuf Frans Kartoma; Novi Theresia Kiak; Maria Indriyani Hewe Tiwu (Universitas 45 Surabaya, 2024)
This research aims to explain the implementation of the policy on the use of Electronic Data Capture (EDC) machines among restaurant taxpayers in Kupang City and to explain the factors that hinder and obstruct the implementation process as well as the use of EDC machines as a payment transaction system for restaurant taxpayers in Kupang City. This study employs a descriptive qualitative approach by conducting interviews with informants from the Badan Pendapatan Daerah Kota Kupang, Bank NTT KCU Kupang, and restaurant taxpayers who have installed EDC machines. The research findings indicate that the policy on the use of Electronic Data Capture (EDC) faces several issues, both in the implementation process and in the use of EDC machines by restaurant taxpayers who have installed them. The lack of awareness, support, and readiness from restaurant taxpayers in terms of technical, administrative, and human resources aspects, as well as ineffective communication and coordination between Bapenda and Bank NTT towards taxpayers, are obstacles in the implementation process of EDC machines. From the perspective of EDC machine usage, technical problems with the machines, such as frequent errors, consumers' understanding level, the billing and tax payment system that is not yet fully digitized through the EDC machine system, the limitations of EDC machine features and services that do not yet meet the needs of restaurant taxpayers, and the human resource aspect of restaurant taxpayers who are not yet able to operate the EDC machines, constitute several non-technical factors that also hinder the use of EDC machines as a payment transaction system. Keywords: , , E